HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN UNSAFE ACTION PADA PEKERJA KETINGGIAN DI PT. X KOTA BATAM - Noviyanti Noviyanti; Yessi Azwar; Ahmad Afif Rizky Pratama (Universitas Pahlawan Tuanku Tambusai, 2022)
Unsafe action is a failure to follow adequate and accurate work requirements and procedures that cause an accident could occur, such as actions without qualification and authority, the completeness of PPE (Personal Protective Equipment), failure to save the equipment, and working g at a very dangerous speed. Factors causing unsafe action can arise from various aspects of knowledge and attitudes. This study aimed to determine the relationship between knowledge and attitudes among Unsafe ActionActionsight workers at PT X Batam. This type of research is a quantitative study with a cross cross-sectional. The population in this study is the height workers at PT. X Batam. A total of 30 respondents are the sample, while the total sampling technique is through h chi-square tests. The research instrument used is a questionnaire The results of this study indicate that there is a relationship between the knowledge factor and unsafe action (p-value = 0.002), and there is a relationship between the attitude factor and unsafe action (p-value = 0.000). The conclusion of the two variables shows that there is a p-value < = 0.05 that Ho is rejected, which means that there is a relationship between factors and unsafe action for height workers. This study result also suggests companies carry out K3 supervision and provide education in the form of increasing Occupational Safety and Health (K3) training programs to increase understanding and awareness of workers' attitudes towardtowardmportance of Occupational Safety and Health (K3). Keywords: Altitude, Unsafe Action